Sperm rheotaxis as a parameter for laboratory Evaluation of frozen semen in bull - Mofadel, Haitham A.; Hussein, Hassan A.; Fath El-Bab, Ahmed M.R.; El‑Sherry, Taymour M. (Journal of Advanced Veterinary Research, 2024)
Sperm rheotaxis is a sperm guidance mechanism that helps to guide and select high-quality sperm cells within the female reproductive tract. Semen is usually evaluated using either the traditional subjective method of evaluation or computer assisted sperm analysis (CASA). These methods provide information about sperm concentration, viability and motility parameters and ignoring sperm ability to travel inside the female reproductive tract. Our goal was to detect the individual variations between different sires through evaluation of post thawed frozen semen using sperm rheotaxis. We studied sperm rheotaxis and sperm kinematics inside microfluidic platforms together with subjective semen analysis (motility, viability, and sperm morphology) in post-thawed bull frozen semen in different sires. The results showed that the positive rheotaxis (PR) was higher in the post-thawed frozen semen of some bulls (P < 0.05) than in others. Our results also revealed that the bulls with the higher PR% have significantly higher straight-line velocity (VSL) and subjective analysis parameters (motility and viability) (P < 0.05) than bull with the lower PR. Furthermore, PR was positively correlated with VSL (r = 0.67, P < 0.0001) and with subjective motility and viability (r =0.57, P = 0.007 and r = 0.49; P= 0.02, respectively). Thus, we concluded that sperm rheotaxis should be used as a new parameter in evaluation of post-thawed frozen semen quality in bull.